A Case Study of Surface Roughness Improvement for C40 Carbon Steel and 201 Stainless Steel using Ultrasonic Assisted Vibration in Cutting Speed Direction - Nguyen, Thanh Trung; Tuan, Truong Cong; Vu, Toan Thang (Engineering, Technology & Applied Science Research, 2024)
The surface roughness of mechanical parts plays an important role in evaluating the machining performance. However, achieving fine surface finishes on small-diameter shafts through traditional lathes poses challenges due to low cutting speed and workpiece stiffness. To address this issue, in the present work, we applied ultrasonic-assisted vibration aligned with the cutting speed direction to enhance the turning process of small shafts made of C40 Carbon steel or 201 stainless steel. The workpieces were machined by Ultrasonic Assisted Turning (UAT) at three different cutting speeds, ranging from 15 to 36 m/min, while maintaining a constant feed rate and depth of cut. To facilitate comparison with conventional turning (CT), the cutting parameters remained consistent, and both methods were performed for the same duration. UAT necessitates the use of a specialized turning inserts’ fixture known as a horn to transmit ultrasonic vibrations from the generator to the tooltip. This study also presents the design methodology and the performance evaluation of the horn. Surface roughness was assessed using the arithmetical mean height, Ra. In UAT, the roughness Ra exhibited the most significant reduction for C40 Carbon steel, reaching a decrease of 308% at a cutting speed of 15 m/min, whereas for 201 stainless steel, Ra did not vary by more than 23% across different cutting speeds.